ByzRev 02.2020.020: Hylkje de Jong, Ἐντολή (mandatum) in den Basiliken: (Legal History Library 31). Leiden -- Boston: Brill 2020. - Chitwood, Zachary (The Byzantine Review, 2020)
Hylkje de Jong, Ἐντολή (mandatum) in den Basiliken (Legal History Library 31). Leiden – Boston: Brill 2020. XII, 239 pp. – ISBN: 978-90-04-41395-5 (€ 94,-)